Thermogravimetric studies of the decomposition kinetics of four different Hevea rubber clones using Ozawa's approach - Medeiros, Eliton Souto de; Moreno, Rogério M. B.; Ferreira, Fábio C. [UNESP]; Alves, Neri [UNESP]; Job, Aldo E. [UNESP]; Gonçalves, Paulo S.; Mattoso, Luiz H. C. (My University, 2003)
Thermal degradation of natural rubber extracted from four different rubber clones of the Hevea brasiliensis species was investigated by thermogravimetry using Ozawa's approach to assess the kinetic parameters of the decomposition process. The results are discussed in terms of the order of reaction, kinetic parameters such as activation energy as a function of conversion degree, and thermal stability for each of the clones.
Keywords: Activation energy; Decomposition; Plasticity; Pyrolysis; Reaction kinetics; Thermodynamic stability; Thermogravimetric analysis; Degree of conversion; Hevea brasiliensis; Plasticity retention index; Rubber